PENAMBAHAN TEPUNG KULIT BUAH NAGA MERAH (Hylocereus polyrhizus) SEBAGAI SUMBER ANTIOKSIDAN PADA MAKANAN SEREAL - Fatma, Fatma; Devitria, Rosa; Putri, Rahayu Nadia; Elfia, Mega; Yesti, Yulia (Ensiklopedia of Journal, 2025)
Dragon fruit is one of the plants that has a high antioxidant content. Consumption of red dragon fruit only utilizes the fruit, while the skin waste which amounts to 30-35% of the fruit weight is underutilized. This study aims to determine whether the addition of red dragon fruit peel flour in cereal foods can increase antioxidant content using the DPPH (2,2-diphenyl-1-1-picrylhydrazyl) method. The inhibition power against oxidation through the antioxidant content test of red dragon fruit peel flour is 50.84%, and the inhibition power against oxidation obtained through the antioxidant content test of red dragon fruit peel flour and cereal is 25.83%. The sensory test results conducted on the taste test of 20 untrained panelists proved that the red dragon fruit peel flour could be well received by the panelists. The antioxidant inhibition level which is not too high with a value of 51% provides an opportunity for red dragon fruit peel as a natural antioxidant ingredient in food. The test results of the addition of red dragon fruit peel flour still have potential as a food additive that contains antioxidants and can be well received by people. Keywords: Dragon Fruit, Antioxidants, Cereals